DETERMINANT FACTORS IN ISLAMIC EDUCATION: A PHILOSOPHICAL PERSPECTIVE - Mulyani, Sri; Marjuni, Andi; Achruh, Andi (LPPM Sekolah Tinggi Ilmu Tarbiyah Al Marhalah Al Ulya Bekasi, Indonesia, 2025)
Islamic education is a crucial component of the education system, aiming to shape Muslim individuals who are both morally upright and knowledgeable. From a philosophical perspective, several factors influence the implementation of Islamic education and provide a strong philosophical foundation for its development. This study aims to identify the determinant factors of Islamic education within the framework of philosophy. This study is a library research, focusing on studies that discuss the determinant factors of Islamic education from a philosophical standpoint. The data for this study were obtained from research conducted and published in reference books as well as national and international journals. The findings indicate that the determining factors in Islamic education include educators, learners, educational objectives, educational tools, and the environment. This research provides a comprehensive understanding of the factors that influence Islamic education within the context of philosophy, as well as their relevance in shaping the character and personality of Muslims. The philosophical implications of these factors can assist educators, educational institutions, and policymakers in applying a holistic approach to designing an education system that not only focuses on academic aspects but also encompasses spiritual, moral, and social dimensions, in line with the vision of holistic Islamic education.